Educação para a cidadania: o papel da leitura na formação da competência linguístico-discursiva dos educadores do campo. - Ramos, Rosilândia Flávia de Lima (2016)
The main objective of this research is to analyze the conception of reading the field educator. The specific objectives seek to investigate the course of the contributions to a educational formation in accordance with the specifics of the field and check the reading activities, held in the Portuguese language discipline, developed in a dialogical perspective. The theoretical methodological axis is a qualitative character and interpretative. In undertaking such a positioning, we assume that man is not a passive being, but interprets the world consecutively. The research instrument was a questionnaire applied at the end of the course. This questionnaire consists of twenty-four questions, divided into two parts. It was applied to twenty-three students. We do analysis of issues relevant to research and grouped the answers according to the categories analyzed: educational formation and design of reading. The theoretical foundation based on Bakhtin and the circle (2003, 2006); Almeida (2004, 2013); Freire (1980 1987 1996)Silva (1987); Batista (1991); Arroyo (1999); Caldart (2004).The supported theoretical approach Bakhtin that conceives language as a place of interaction between subjects, resulting in more comprehensive and meaningful practice the act of reading, on special terms in that reading involves elements of the socio-historical context and ideological of individuals. Verified that the teaching of reading may not be performed outside the dialogical context, because we believe that This perspective provides students the critical and reflective postures field.